Resultados del año APEC Perú 2024. La recuperación del consenso y el avance de la Visión Putrajaya 2040 - Vásquez Corrales, Carlos (2024)
The article begins with a situational analysis of APEC prior to the meetings in Peru in 2024, specifically, on the impossibility of reaching consensus in the last two meetings of this forum(in 2022 and 2023) to adopt deliverables that were sufficiently reliable and legitimate, as well as the factors that contributed to this. After this, the study focuses on developing the strategy deployed by the Ministry of Foreign Affairs of Peru to overcome these difficulties and recover the necessary consensus that allowed the adoption of 20 deliverables. These documents will allow this forum to advance in the implementation of the Putrajaya Vision 2040.